1988
DOI: 10.1302/0301-620x.70b1.3339064
|View full text |Cite
|
Sign up to set email alerts
|

Elastic stable intramedullary nailing of femoral shaft fractures in children

Abstract: We report the use of elastic stable intramedullary naffing (ESIN) in 123 fractures of the femoral shaft in children. Flexible rods are introduced through the distal metaphyseal area, and the aim is to develop bridging callus. Early weight-bearing is possible and is recommended. There was one case of bone infection and no delayed union. Complications were minimal, the most common being minor skin ulceration caused by the ends of the rods. A surprising feature was the low incidence of growth changes, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
368
4
23

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(409 citation statements)
references
References 2 publications
14
368
4
23
Order By: Relevance
“…In addition, patients with concomitant lower extremity fractures can be mobilized more rapidly because of the increased ability to weight bear through the extremity. The surgical technique is straightforward and is familiar to most pediatric orthopedists due to its widespread use in the treatment of other fractures in children [18,[21][22][23][24][25][26][27]. Surgical stabilization of humeral shaft fractures in children, when indicated, can be safely performed using titanium elastic nails.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, patients with concomitant lower extremity fractures can be mobilized more rapidly because of the increased ability to weight bear through the extremity. The surgical technique is straightforward and is familiar to most pediatric orthopedists due to its widespread use in the treatment of other fractures in children [18,[21][22][23][24][25][26][27]. Surgical stabilization of humeral shaft fractures in children, when indicated, can be safely performed using titanium elastic nails.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have recommended using the largest nail diameter possible; however, the larger the nail, the more difficult it is to contour and insert. The recommended use of two flexible nails each with a diameter, i.e., 40% of the medullary canal diameter will yield a ''canal fill'' of 80% [4,9,10]. A recent study found that an 80% canal fill improved the overall biomechanical stability of the fractured femur, but often resulted in malreduction with posterior gapping [18].…”
Section: Introductionmentioning
confidence: 99%
“…The flexible intra-medullary nailing method allows early weight bearing, rapid healing and minimal disturbance of bone growth [10] . This method has gained widespread acceptance as a safe, minimally invasive and cost effective method of treatment in children 5-15 years of age [10][11][12][13] .…”
Section: Flexible Intramedullary Nail Fixation In Paediatric Femoral mentioning
confidence: 99%
“…This method has gained widespread acceptance as a safe, minimally invasive and cost effective method of treatment in children 5-15 years of age [10][11][12][13] .…”
Section: Flexible Intramedullary Nail Fixation In Paediatric Femoral mentioning
confidence: 99%